Base de dados em eletroencefalografia (EEG) - Costa, Patrícia Gonçalves da (2022)
Comatose patients’ treatment involves not only caring for their basic organic homeostasis, but also rehabilitation and awakening from coma. In this context, cognitive stimulation performed during hospitalization, such as music therapy, may be considered of paramount relevance in the patient life quality, just after the Intensive Care Unit (ICU) hospitalization. This dissertation summarizes the development of a database, for which clinical data and EEG examination of 62 comatose patients were collected. These were subjected to different musical stimulations, the procedure being performed on critically ill patients of the Adult ICU (AICU), Uberlandia Clinic Hospital (HCU), during 2018-2019. The general clinical profile of these patients was assessed, and the particular profile of patients who died was compared with that of patients who left the AICU after their hospitalization. A musical stimulation protocol was developed, adapted to the context of the Brazilian Public Health System (SUS), taking into account requirements such as methological precision, noise suppression, ethics involved during collection, and minimal interference in medical routines. A simple example of a quantitative study was carried out, yielding that, even in the context of a long musical stimulation (8 min), the changes in the bioelectric activity in terms of spectral power are generally low, occurring in only a few electrodes, and concentrating on the delta wave.